Writing Training in ISBN-Based Books Based on Local Wisdom - Rambe, Elismayanti; Khoirun Nisa, Ardina; Wahyuni, Rahmi; Susanti Hasibuan (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The limited capacity to write books based on local wisdom in Mandailing Natal Regency presents a serious challenge to literacy development and cultural preservation. Despite its rich cultural heritage and strong traditional values, much of this local wisdom remains undocumented in professionally published books. Many community members, including educators, lack adequate skills in manuscript writing and publishing. This Community Partnership Program (PKM) aims to enhance the ability of teachers and the wider community in Mandailing Natal Regency to write and publish ISBN-registered books that focus on local wisdom and cultural heritage. The program provides participants with theoretical knowledge and practical skills covering the entire book-writing process, including idea development, data collection, manuscript writing, editing, layout design, publishing procedures, ISBN registration, copyright, and ethical writing. The training employed lectures, discussions, case studies, and hands-on practice supported by intensive mentoring from experienced facilitators. Conducted over four weeks, the program involved 60 participants, comprising students, university students, teachers, librarians, and literacy activists. The results showed meaningful outcomes: all participants produced draft manuscripts related to Mandailing Natal local wisdom, and 18 drafts met publication standards and were compiled into one ISBN-registered book. Evaluation results also revealed a 30% increase in average pretest and posttest scores, indicating an improvement in understanding and writing competence. Overall, the program makes a positive contribution to strengthening literacy and preserving local wisdom in the Mandailing Natal Regency.